Influence of dietary different levels of zinc oxide nano particles on the yield and quality carcass of broiler chickens during starter stage - KHAH, MEHRAN MOHAMMADI; AHMADI, FARHAD; AMANLOU, HAMID (The Indian Journal of Animal Sciences, 2015)
The aim of the present study was to evaluate the effect of dietary different levels of zinc oxide nanoparticles (Zno-NPs) on the yield and quality carcass of broiler chickens during starter stage (from 1 to 21 day). One-day mail broilers (300) were distributed in a completely randomized design (CRD) in 5 treatment groups, each having 4 replicates and 15 birds in each experimental pen. The experimental diets were: T1 control (basal diet); T2, T3, T4 and T5 diets, supplemented with 30, 60, 90 and 120 mg Zno-NPs/kg of diet, respectively. Birds had access to feed and water throughout time of research. On d 21 birds (4;1 bird/replicate) were randomly selected, slaughtered and then carcass yield, breast and thigh composition were evaluated. The results indicated that live body weight, dressing and percentage of breast and thigh meat were higher in the T3 and T4 groups than control and other groups. Dry matter (DM), and crude protein (CP) of breast and thigh meats were higher in T3 (60 mg Zno-NPs/kg) and T4 (90 mg Zno-NPs/kg) bird groups as compared to control and other treatments. Ether extract in breast and thigh meat reduced in comparison with control treatment. In conclusion, results of present trial suggested that dietary no-NPs with 60 and/or 90 mg/kg Zno-NPs had significantly improved broiler quality and quantity of carcass broiler during starter period.